New Approach on Statistical Convergence of Triple Sequences in Neutrosophic Normed Spaces - P. Jenifer; M. Jeyaraman (Neutrosophic Sets and Systems)
In this project the triple sequence’s statistical convergence within Neutrosophic normed space is proposed. Also, algebra of statistical limits and statistical cauchy sequences are discussed in this article. Furthermore, the article provides instances to back up a few definitions and theorems. We also looked at the special sequence space’s evidence of completeness.